Survey of bovine brucellosis on the island of Fernando de Noronha, Pernambuco, Brazil - Almeida, Erivânia Camelo de; Souza, Marcília Maria Alves de; Lima Filho, Carlos Diógenes Ferreira; Magalhães, Fernando Jorge Rodrigues; Pontual, Késia Alcântara Queiroz; Fonsêca, Filipe Sobral; Marvulo, Maria Fernanda Vianna; Dias, Ricardo Augusto; Ferreira, Fernando; Ferreira Neto, José Soares; Silva, Jean Carlos Ramos da (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Considering the lack of information about livestock diseases on Brazilian oceanic islands, the occurrence of bovine brucellosis was investigated on the island of Fernando de Noronha, state of Pernambuco, Brazil. Serum samples were collected in October 2009, from all the 105 cows raised on the island at that time. These were examined concurrently using the Rose Bengal test and the Complement Fixation Test. All the samples were negative in both tests, indicating that the cows on the island were likely free from infection by smooth forms of Brucella. These results can partly be explained by the prohibition of introduction and importation of both small and large-sized animals that had been implemented through District Decree 19 of February 28, 2004.